C-H activation of alkanes on Rh+ n (n=1-30) clusters: size effects on dehydrogenation - Adlhart, Christian; Uggerud, Einar (The Journal of chemical physics, 2005)
The rate coefficients for the dehydrogenation of ethane, propane, and isobutane with cationic rhodium atoms Rh+ and clusters Rh+ n of up to 30 atoms were measured under single-collision conditions in a Fourier-transform ion cyclotron resonance mass spectrometer. The reaction rates are cluster size dependent and parallel for all the three alkanes. While the reactions proceed close to the theoretical collision rates for a large number of clusters, characteristic minima are observed for Rh+ (5/6/9/19/28). The degree of dehydrogenation varies with the cluster size with maxima for 10< or =n< or =15 for the three alkanes and for n=3 and 2-4 in the cases of ethane and propane, respectively. However, complete dehydrogenation is only observed for the reaction of Rh+ 11 with propane. Dehydrogenation is remarkably selective and no other neutral products than H2 are observed. The results are interpreted in terms of likely cluster geometries.